Financial strain moderates genetic influences on self-rated health: support for diathesis–stress model of gene–environment interplay. (2nd January 2022) - Finkel, Deborah; Zavala, Catalina; Franz, Carol E.; Pahlen, Shandell; Gatz, Margaret; Pedersen, Nancy L.; Finch, Brian K.; Dahl Aslan, Anna; Catts, Vibeke S.; Ericsson, Malin; Krueger, Robert F.; Martin, Nicholas G.; et al.
ABSTRACT: Data from the Interplay of Genes and Environment across Multiple Studies (IGEMS) consortium were used to examine predictions of different models of gene-by-environment interaction to understand how genetic variance in self-rated health (SRH) varies at different levels of financial strain. A total of 11, 359 individuals from 10 twin studies in Australia, Sweden, and the United States contributed relevant data, including 2, 074 monozygotic and 2, 623 dizygotic twin pairs. Age ranged from 22 to 98 years, with a mean age of 61.05 (SD = 13.24). A factor model was used to create a harmonized measure of financial strain across studies and items. Twin analyses of genetic and environmental variance for SRH incorporating age, age 2, sex, and financial strain moderators indicated significant financial strain moderation of genetic influences on self-rated health. Moderation results did not differ across sex or country. Genetic variance for SRH increased as financial strain increased, matching the predictions of the diathesis–stress and social comparison models for components of variance. Under these models, environmental improvements would be expected to reduce genetically based health disparities.